Generalized Additive Models of Climatic and Metabolic Controls of Subannual Variation in pCO2 in Productive Hardwater Lakes. Issue 6 (27th June 2018) - Wiik, E.; Haig, H. A.; Hayes, N. M.; Finlay, K.; Simpson, G. L.; Vogt, R. J.; Leavitt, P. R.
Abstract: Spatiotemporal variation in climate and weather, allochthonous carbon loads, and autochthonous factors such as lake metabolism (photosynthesis and respiration) interacts to regulate atmospheric CO2 exchange of lakes. Understanding this interplay in diverse basin types at different timescales is required to adequately place lakes into the global carbon cycle and predict CO2 flux through space and time. We analyzed 18 years of data from seven moderately hard lakes in an agricultural prairie landscape in central Canada. We applied generalized additive models and sensitivity analyses to evaluate the roles of metabolic and climatic drivers in regulating CO2 flux at the intra‐annual scale. At mean conditions with respect to other predictors, metabolic controls resulted in uptake of atmospheric CO2 when surface waters exhibited moderate primary production but released CO2 only when primary production was very low (<8 μg/L or when dissolved nitrogen was elevated (>2, 000 μg/L), implying that respiratory controls offset photosynthetic CO2 uptake under these conditions. Climatically, dry conditions increased the likelihood of in‐gassing, likely due to evaporative concentration of base cations and/or reduced allochthonous carbon loads. While more research is required to establish the relative importance of climate and metabolism at other timescales (diel, autumn/winter), we conclude that these hard fresh waters characteristic of continental interiors are mainly affected by metabolic drivers of pCO2 at daily‐monthly timescales, are climatically controlled at interannual intervals, and are more likely to in‐gas CO2 for a given level of algal abundance than are soft water, boreal ecosystems. Key Points: In Canadian hardwater prairie lakes, calculated CO2 fluxes correlate mostly with pH, not DIC Intra‐annual CO2 correlates with algal abundance (‐CO2 ) and prolonged clearwater phases (+CO2 ) CO2 influx increases with drier weather conditions and is reduced with extreme N loading